Treatment Modalities in Breast Cancer: An Overwiew - Adiga, Usha; Adiga , Sachidananda; Rai, Tirthal; Desy, T. M. (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
Worldwide, there is a significant disparity in breast cancer survival rates. To manage tumors, various contemporary medications are prescribed. Breast cancer may be prevented in people who are more likely to have it by medical treatment with antiestrogens such as raloxifene or tamoxifen. A further preventive strategy in cases where a woman's risk of acquiring cancer is higher has both breasts surgically removed. Diverse management options, such as adjuvant therapy, hormonal therapy, radiation therapy, immunotherapy, monoclonal antibodies against breast cancer and combination chemotherapy are employed on individuals diagnosed with breast tumors. Gene therapy, stem cell therapy and anti-angiogenesis drugs are in trials for managing of breast cancer. Management for people with distant metastases typically focuses on improving survival rates and quality of life. One of the main drivers for finding alternative treatments is the severe side effects of breast cancer treatment.